MANAGEMENT OF ESOPHAGOGRAPHY EXAMINATION TECHNIQUES WITH THE OBSTRUCTION CLINIC AT THE RADIOLOGY INSTALLATION OF THE ARIFIN ACHMAD UMUM DAERAH HOSPITAL, RIAU PROVINCE - Radita Nugraha; Wenda Erliyanda; Nurhikmah (LPPM Universitas Awal Bros, 2025)
Background: Esophageal obstruction is a condition that causes dysphagia due to narrowing or blockage of the esophageal lumen, requiring contrast radiographic examination to evaluate the anatomy and function of the upper gastrointestinal tract. Esophagography is a fluoroscopic examination using barium sulfate contrast medium that can demonstrate both morphological abnormalities and esophageal motility disorders. Theoretically, the examination is performed using several standard projections, namely anteroposterior (AP), right anterior oblique (RAO), lateral, and left anterior oblique (LAO). However, in clinical practice at several hospitals, the examination procedure is often modified according to the patient's condition and diagnostic requirements. Therefore, an evaluation of its implementation is necessary. This study aimed to analyze the management of the esophagography examination technique in patients with clinically suspected esophageal obstruction at the Radiology Department of Arifin Achmad Regional General Hospital, Riau Province. Methods: This study employed a descriptive qualitative design with a case study approach. Data were collected through direct observation of the examination procedure, interviews with radiographers, and documentation of radiographic findings conducted from June to July 2024. The data were analyzed descriptively by comparing the actual examination procedure with the established theoretical standards. Results: Esophagography in patients with clinically suspected esophageal obstruction was performed using AP plain, post-contrast AP, and lateral projections with barium sulfate contrast medium under fluoroscopic guidance. The findings showed that the use of the two primary projections (AP and lateral) was sufficient to demonstrate the esophageal anatomy and identify the location of the obstruction, thereby fulfilling the diagnostic requirements. However, the procedure did not fully comply with the theoretical standard, which recommends the additional use of RAO and LAO projections to provide more optimal visualization of the esophagus.